2017
DOI: 10.1111/irfi.12162
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Firm‐Level Illiquidity on Crash Risk and the Role of Media Independence: International Evidence

Abstract: This study investigates the impact of firm-level illiquidity on stock price crash risk by employing a sample of 21,986 firms across 36 countries spanning the years 1997 to 2007. In doing so, the role of media independence in shaping this impact is also examined. The empirical results suggest that stock illiquidity is significantly and positively associated with firm-level crash risk. Furthermore, the positive association between illiquidity and crash risk has been mitigated in countries with independent media,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 88 publications
(121 reference statements)
0
1
0
Order By: Relevance
“…Stoll et al suggested that stock attributes such as market value, volume and volatility can significantly reshape the stock illiquidity [15,16,17]. On the other hand, An et al found that macro economic factors such as media independence, policy uncertainty, default risk and funding conditions have a remarkable impact on illiquidity [18,19,20,21]. These evidences imply that stocks can be well profiled in terms of illiquidity and more importantly, external shocks to the market can also be absorbed and thus sensed through illiquidity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Stoll et al suggested that stock attributes such as market value, volume and volatility can significantly reshape the stock illiquidity [15,16,17]. On the other hand, An et al found that macro economic factors such as media independence, policy uncertainty, default risk and funding conditions have a remarkable impact on illiquidity [18,19,20,21]. These evidences imply that stocks can be well profiled in terms of illiquidity and more importantly, external shocks to the market can also be absorbed and thus sensed through illiquidity.…”
Section: Literature Reviewmentioning
confidence: 99%